Gambaran Keefektifan Penggunaan Media Kartu dalam Meningkatkan Komunikasi Interpersonal - Cici Yulia (Program Studi Bimbingan Konseling Islam Fakultas Dakwah Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2021)
Communication is an inseparable part of human life, anybody can’t live without communication. As social beings who always interact with the environment, communication skills are needed, especially interpersonal communication. Devito (2007) explains, interpersonal communication is the communication that takes place between two persons who have an established relationship; the people are in some way connected, often interpersonal communication takes place face to face:This is the type of interaction that probably comes to mind when you think of conversation. The purpose of this study is to reveal the effectiveness of tehnique card media to improve interpersonal communication by using an experimental research model of one group pre test-post test design with a sampling technique that is purposive sampling. The results showed that there was a difference between the results of the pre-test and post-test with the acquisition of the Wilcoxon test results, namely the value of Zhitung 2.812 > Ztabel 1.960 indicating that Ho was rejected and Ha was accepted, so it can be concluded that the use of technique card media is effective to improve students' interpersonal communication